Penerapan Sistem Berbasis Web Dalam Penerimaan Murid Baru Pada SMA Markus Medan - Panggabean, Tongam E (JURIKOM (Jurnal Riset Komputer), 2018)
Technology is no longer a sentence that is foreign to people who stir in the computer world and not surprising if it will be found in places that provide facilities / facilities to access the internet, not only that even the general environment of the company is now beginning to open the network for Internet services in publishing company, as well as in At Sekolah Tinggi Markus Medan. For that writer make a website to pempubikasian accurate and fast information about High School Markus Medan. In the making of this website the author uses Joomla which is a CMS (Content Management Syste) created using PHP programming language (Personal Home Page) and Apache XAMPP web server as localhost server and system database